ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Elisabeth Andini H; H. Sri Sulistyanto (Universitas Katolik Soegijapranata Semarang, 2011)
The research concerning with earning management, has been conducted by many researcher. The earning management topic has become interest jor many researcher because it's urgency in .financial. This research is try to improve previous research conducted by Wedari (2004) dan Midiastuty dan Machfoedz (2003), by involving new variable, auditors quality, as GCG mechanism which yang proxied with Bigfour Accountingfirm and non Big/our. The result is: Audit committee, institutional and auditor quality doesll't have influence to earning management, while commissioner board proportion and managerial ownership influencing earning management.